The chemistry of nanomaterial and nanobiomaterial - Hussein, Mohd. Zobir (Universiti Putra Malaysia Press, 2009)

(untitled)
Nanomaterials and nanobiomaterials are materials which are currently subject to intense research while at the same time their usage in development of various technological applications is also moving at a very swift pace. Advances in this area of research are consequent to the realization that nanomaterials and nanobiomaterials have profound influence on improvement of various aspects of life quality as well as other industrial aspects. Layered two dimensional inorganic materials, especially layered double hydroxides (LDH) have versatile properties due to its intercalation and deintercalation characters. By hybridization of LDH with beneficial functional active agents, various new host-guest nanohybrids with tailor made properties can be generated. If the guest is a biomaterial such as DNA or plasmid, then the nanohybrid can be used as vector for plasmid transfaction. On the other hand, if a drug is encapsulated into the LDH interlamellae, then the nanohybrid can be used as a controlled release formulation. On the other hand, if active agents such as herbicides, plant growth regulators, etc. are used, then a new generation of agrochemicals which is safer, user- and environmentally-friendly can be generated. LDH composed of nickel calcined at high temperature of around 800 oC is suitable to be used as the catalyst precursor for carbon nanotubes preparation. This is due to the better dispersion of the nickel nanoparticles used for the formation of multiwalled carbon nanotubes. This work provides understanding of some important fundamental considerations necessary for the design and formation of new functional materials especially nanomaterials and nanobiomaterials of nanohybrid type. The materials can be used to store beneficial agents in the nanolayered interlamellae, transport it to the target and subsequent controlled release. In addition, using biomaterial such as bacteria as biotemplating agents coupled with the hydrothermal method to generate new nanostructured materials open up new methods of synthesis by the green chemistry route. These offer avenues for a new class of nanomaterials with physical and chemical properties that can be tailor made.